Use of Zoledronic Acid in Paediatric Craniofacial Fibrous Dysplasia - Chiara Di Pede; Sabrina Congedi; Sara Rossin; Antuan Divisic; Alesandra De Gregorio; Caterina Agosto; Igor Catalano; Alessandro Mazza; Leonardo Sartori; Stefano Masiero; Franca Benini (Case Reports in Pediatrics)
We describe a case of a paediatric patient affected by mandibular fibrous dysplasia (FD) with severe and chronic pain who was successfully treated with zoledronic acid (ZOL): a third-generation bisphosphonate. Further research is needed to assess its safety and efficacy as a treatment option for FD in the paediatric population.